High‐resolution molecular genomic autopsy reveals complex sudden unexpected death in epilepsy risk profile. Issue 2 (24th December 2013) - Klassen, Tara L.; Bomben, Valerie C.; Patel, Ankita; Drabek, Janice; Chen, Tim T.; Gu, Wenli; Zhang, Feng; Chapman, Kevin; Lupski, James R.; Noebels, Jeffrey L.; Goldman, A.M.
Summary Advanced variant detection in genes underlying risk of sudden unexpected death in epilepsy (SUDEP) can uncover extensive epistatic complexity and improve diagnostic accuracy of epilepsy‐related mortality. However, the sensitivity and clinical utility of diagnostic panels based solely on established cardiac arrhythmia genes in the molecular autopsy of SUDEP is unknown. We applied the established clinical diagnostic panels, followed by sequencing and a high density copy number variant (CNV) detection array of an additional 253 related ion channel subunit genes to analyze the overall genomic variation in a SUDEP of the 3‐year‐old proband with severe myoclonic epilepsy of infancy (SMEI). We uncovered complex combinations of single nucleotide polymorphisms and CNVs in genes expressed in both neurocardiac and respiratory control pathways, including SCN1A, KCNA1, RYR3, and HTR2C. Our findings demonstrate the importance of comprehensive high‐resolution variant analysis in the assessment of personally relevant SUDEP risk. In this case, the combination of de novo single nucleotide polymorphisms (SNPs) and CNVs in the SCN1A and KCNA1 genes, respectively, is suspected to be the principal risk factor for both epilepsy and premature death. However, consideration of the overall biologically relevant variant complexity with its extensive functional epistatic interactions reveals potential personal risk more accurately.